Density Functional Theory and Antimicrobial Studies on tris(N-Furfuryl-N-benzyldithiocarbamato-S,S′)antimony(III) - Tamilvanan, Sundaramoorthy (Asian Journal of Chemistry, 2022)
In present work, the complex, tris(N-furfuryl-N-benzyldithiocarbamato-S,S′)antimony(III) has been synthesized and characterized by elemental analysis, IR, 1H NMR, 13C NMR and biological studies. In the theoretical calculations, the DFT method with the B3LYP hybrid functional using the LAN2DZ basis set has been selected as a computational technique. The molecular structure and spectral are explained by Gaussian computational analysis theory (B3LYP) are found to be in correlation with the experimental data observed from the various spectrophotometric methods. 1H NMR and 13C NMR were performed by using GIAO (Gauge Independent Atomic Orbital) process with the B3LYP method and the LAN2DZ basis set and NMR chemical shifts related to TMS were compared. The molecular orbital calculations such as HOMO-LUMO energy gap, Mulliken population analysis and MEP surfaces have been calculated. Further, the synthesized antimony dithicarbamate complex has been evaluated for in vitro antimicrobial activity against various microorganisms using the disc diffusion method. The results represented that the studied molecule has shown the antimicrobial activity.